Pemberdayaan Masyarakat Melalui Penguatan Skill Pelestarian Warisan Budaya Dawet Jabung Ponorogo di Era Digital: Community Empowerment Through Strengthening Skills in Preserving Ponorogo's Dawet Jabung Cultural Heritage in the Digital Era - Wijianto Wijianto; Fery Setiawan; Niken Hilvanda Putri; Yasmin Shafa Nadiyah; Evaldo Aryastya Faadhilah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Culinary cultural heritage is an important part of local identity that needs to be sustainably preserved amid the dynamics of modernization. Dawet Jabung, a culinary specialty of Jabung Village, Ponorogo Regency, faces challenges in the form of shifting preferences of the younger generation and low collective awareness in cultural preservation efforts. This community service activity aims to increase community understanding, awareness, and participation in preserving Dawet Jabung as a local culinary cultural heritage. The service program is implemented through an educational approach grounded in cultural knowledge and experience, manifested in cultural preservation seminars, digital media utilization training, social media optimization workshops, and creative activities that engage various community elements, including PKK mothers and early childhood. The implementation method is carried out in stages: preparation, implementation, and evaluation, with active involvement of partners in each activity. The results of the activity show an increase in community awareness and involvement in Dawet Jabung preservation efforts, characterized by active partner participation, the emergence of cross-village collaboration, and a growing sense of ownership of local culinary culture. This activity also demonstrates that an educational and participatory approach can be an effective initial strategy in maintaining the sustainability of culinary cultural heritage at the village level. Overall, this community service program makes a positive contribution in encouraging the preservation of local culinary culture by strengthening the role of the community and community collaboration.